(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
In this paper, we aim to investigate separation axioms in intuitionistic topological spaces. After presenting some characterizations of separation axioms, we provide interrelationships among those and their non-implications in counterexamples. Furthermore, we show that our notions satisfy hereditary and topological properties. Moreover, we establish that some of these notions satisfy productive and projective properties. 2000 Mathematics Subject Classification. 54A99. J. Bangladesh Acad. Sci. 48(1); 35-43: June 2024